2014
DOI: 10.1111/aos.12460
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and outcomes in refractive lens exchange surgery

Abstract: ABSTRACT.Purpose: To assess demographics and refractive outcomes in patients undergoing refractive lens exchange surgery (RLE), with a population of cataract patients as a reference. Methods: A RLE cohort from a private eye clinic (n = 675) and a cataract cohort from the outcome registration of the Swedish National Cataract Register were studied and compared from an epidemiological perspective regarding age, gender, preoperative refraction and postoperative refractive outcome. Results: The RLE patients were yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…As such, one would expect similar objective outcomes although subjective patient reporting might be expected to be slightly worse for the RLE cases, since they have been reported to have higher expectations relative to their vision after IOL implantation 19. We did not see any subjective differences in our study.…”
Section: Discussionmentioning
confidence: 50%
“…As such, one would expect similar objective outcomes although subjective patient reporting might be expected to be slightly worse for the RLE cases, since they have been reported to have higher expectations relative to their vision after IOL implantation 19. We did not see any subjective differences in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Although more and more surgeons are opting to perform RLE on presbyopes younger than 50 years, 12 14 to our knowledge, no study has specifically compared the visual, refractive, and quality of life outcomes among different age categories of RLE patients. Younger presbyopes are more active, working-age patients with high visual requirements for near and intermediate vision.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of MIOLs, presbyopia can be corrected by crystalline lens exchange, that is, RLE [ 15 ]. Patients who undergo RLE generally are younger [ 5 ] and have higher expectations regarding refractive and visual outcomes than those with cataracts. To enable patients to be spectacle-free while engaging in daily activities, the MIOL must provide adequate functional vision at various distances.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intermediate vision, which is important for most people in daily activities, for example, computer use, shopping, and cooking, was rarely reported [ 3 ]. Westin et al [ 5 ] compared a group of patients who underwent RLE in a clinic setting with a population from a cataract surgery registry and found that the former group was significantly younger. Since younger presbyopic patients seeking RLE are less likely to have complaints at intermediate distance and implantation of diffractive bifocal MIOLs can lead to the loss of natural accommodation, the overall impact of RLE is unknown.…”
Section: Introductionmentioning
confidence: 99%